Analisis Algoritma Definite Integration Menggunakan Metode Desk Check - Inna Muthmainnah Dalimunthe; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Normally we experience hardships in deciding the result of a pseudocode calculation, particularly in settled control structures or settled circles. Generally muddled. We experience issues speculating rationale or deciding the result. For instance, what is the final product of the cycle? Is that correct? Where are the beginning and end points of the circle? Where could the limit of the circle's body be? Should this cycle proceed or stop? Does the circle go on until the outcome or intelligent condition is valid? Does the circle run until the condition is valid? Aside from that, in light of the fact that the human psyche has impediments in recollecting or rehashing, a device is expected to examine it. In light of this issue, the creator is searching for a basic model or technique for variable examination, both info factors and result factors with algorithmic rationale in a pseudo code calculation. This is the creator's goal in planning a table called a control table. For this situation, the errand of work area control is to report the historical backdrop of a few changes and their rationale of the different investigated factors, as well as data sources and results, with the assistance of tables. The reason for this paper is to dissect the reaction to the plan of the Specific Reconciliation Calculation utilizing the flowchart technique and inspect potential instances of issues, in particular precise coordination. Keyword : Algoritma Analysis